Strong conservation of the bird Z chromosome in reptilian genomes is revealed by comparative painting despite 275 million years divergence - Pokorná, Martina; Giovannotti, Massimo; Kratochvíl, Lukáš; Kasai, Fumio; Trifonov, Vladimir A; O'Brien, Patricia C M; Caputo, Vincenzo; Olmo, Ettore; Ferguson-Smith, Malcolm A; Rens, Willem (Chromosoma, 2011)
The divergence of lineages leading to extant squamate reptiles (lizards, snakes, and amphisbaenians) and birds occurred about 275 million years ago. Birds, unlike squamates, have karyotypes that are typified by the presence of a number of very small chromosomes. Hence, a number of chromosome rearrangements might be expected between bird and squamate genomes. We used chromosome-specific DNA from flow-sorted chicken (Gallus gallus) Z sex chromosomes as a probe in cross-species hybridization to metaphase spreads of 28 species from 17 families representing most main squamate lineages and single species of crocodiles and turtles. In all but one case, the Z chromosome was conserved intact despite very ancient divergence of sauropsid lineages. Furthermore, the probe painted an autosomal region in seven species from our sample with characterized sex chromosomes, and this provides evidence against an ancestral avian-like system of sex determination in Squamata. The avian Z chromosome synteny is, therefore, conserved albeit it is not a sex chromosome in these squamate species.
Keywords: Male; Sex Chromosomes; Reptiles; malování chromozomů; Animals; ptáci; Birds; mužské pohlaví; Female; Karyotype; pohlavní chromozomy; genom; plazi; Evolution, Molecular; ženské pohlaví; zvířata; Chromosome Painting; fylogeneze; karyotyp; Phylogeny; Genome; molekulární evoluce